The functional relevance of oestrogen-related receptor gene to ultraspiracle gene in regulating the development of Polyrhachis vicina (Hymenoptera: Formicidae). (3rd July 2019) - Xi, Gengsi; Ying, Qiongqiong; Xie, Hui
ABSTRACT: The oestrogen-related receptor ( ERR ) and ultraspiracle ( USP ) genes belong to members of nuclear receptors superfamily, which play some important roles in regulation of insect growth, development and reproduction. In this paper, an USP gene full-length sequence of 1553 bp in Polyrhachis vicina ( P.vicina ) was first cloned and named PvUSP, which contains a 1275 bp open reading frame (ORF) and encodes a protein of 424 amino acids. Then the PvERR and PvUSP mRNA expression levels as well as the ecdysone concentration were investigated at different developmental stages and castes of P.vicina . The changes of PvERR and PvUSP mRNA expressions at whole life cycle of the ants may suggest their function in regulating the development. Ingested RNA interference was performed at all developmental stages and castes of P.vicina to knockdown the PvERR mRNA expressions by continuous feeding of PvERR double-stranded RNA (dsRNA) mixed in artificial diet. Ultimately, the feeding of dsRNA led to the change of PvERR and PvUSP transcript as well as the ecdysone concentration. These results indicated that feeding dsRNA was an efficient method to achieve the gene silencing and to know the functions of target gene. PvUSP may participate in the PvERR signalling pathway and may have functional relevance in regulating the growth and development of P.vicina .